Appointments: Fellow Akademi Profesor Malaysia - UiTM, Fakulti Sains Gunaan (Faculty of Applied Sciences, 2020)
Congratulations to Prof. Ts ChM Dr. Chan Chin Han on his appointment as a Fellow of Akademi Profesor Malaysia, effective 20 June 2020. This prestigious recognition reflects her outstanding contributions to academia, research excellence, and professional service. The appointment is a testament to his dedication, leadership, and continued commitment to advancing higher education and scholarly achievement in Malaysia.